2019
DOI: 10.1002/jcb.29449
|View full text |Cite
|
Sign up to set email alerts
|

LINC00665 induces gastric cancer progression through activating Wnt signaling pathway

Abstract: Long noncoding RNAs (lncRNAs) are recently recognized as noteworthy regulators of different tumors, counting gastric cancer (GC). Lately, long intergenic noncoding RNA (LINC) 00665 has been verified to display significant parts in several cancers. Be that as it may, its role and mechanism in GC movement still stay uninvestigated. As of now, we observed LINC00665 was obviously GC cells (MKN28, BGC‐823, SGC7‐901, AGS, HGC‐27) in comparison to GES‐1 cells, which was identified as human normal gastric epithelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…LINC00665/miR-4458/DOCK1 interactome identification. LINC00665 has been reported to be a tumor promoter in various human cancers, such as lung cancer 31,32 , gastric cancer 17,33 , hepatocellular carcinoma [34][35][36] , and breast cancer 16,37 . However, its effects on AML cells remain unexplored.…”
Section: Resultsmentioning
confidence: 99%
“…LINC00665/miR-4458/DOCK1 interactome identification. LINC00665 has been reported to be a tumor promoter in various human cancers, such as lung cancer 31,32 , gastric cancer 17,33 , hepatocellular carcinoma [34][35][36] , and breast cancer 16,37 . However, its effects on AML cells remain unexplored.…”
Section: Resultsmentioning
confidence: 99%
“…With the development of high-throughput sequencing, dysfunctional lncRNAs are believed as key events for tumor development [21]. Recent studies have shown that LINC00665 exerts a carcinogenic role in many types of tumors [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…LINC00665 triggers lung carcinoma progression by sponging miR-98 and thus mediates the ERK signaling [16]. In addition, LINC00665 is also involved in the progression of gastric cancer and breast cancer [17][18][19]. Its biological function in OC is largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al reported that Linc00665 deletion can inhibit the migration and invasion of triple negative breast cancer cell lines MDA-MB-231 and BT549 ( 12 , 31 ). Gao et al elucidated that Linc00665 knockdown can inhibit the migration and invasion of gastric cancer cell lines AGS and BGC‐823 ( 9 ). Wang et al also reported that Linc00665 silencing can significantly reduce the invasive ability of gastric cancer cell lines AGS and MGC-803 ( 32 ).…”
Section: Discussionmentioning
confidence: 99%